Hematocervix as an Uncommon Complication of Cesarean Delivery: A Case Report - Ozlem ece Basaran; Emine Seda Guvendag Guven; Suleyman Guven (Gynecology Obstetrics & Reproductive Medicine, 2020)
Hematometra is a condition of retained blood or clot in the uterus. If just the cervix is affected by collection, the condition is described as hematocervix. The hematocervix should be suspected in a women with amenorrhea and recurrent lower abdominal pain. The objective of this case report was to report a rare case of isolated hematocervix following cesarean delivery.